Bioprospecting of new Antarctic seaweed selective antitumor molecules: chemical characterization and in vitro analysis - Priscila O. de Souza; Felipe A. Silva; Caroline O. da Silva Frozza; Rafaele Frassini; Mariana Roesch-Ely; Marco A.Z. dos Santos; Rogério A. Freitag; Pio Colepicolo; Claudio M.P. Pereira; Elizandra Braganhol (Elsevier, 2022)
Background: The Antarctic continent exposes seaweeds to extreme environmental conditions, which may facilitate the production of novel metabolites. Algae represent a highly diverse group of little explored organisms. Thus, marine biomass has emerged as a possible source of new biologically active molecules for the treatment of diseases requiring novel therapeutic options. Purpose: The ultrasonic and Soxhlet extractions were used to evaluate chemical profiles and antitumor activities of Desmarestia anceps, Iridaea cordata, and Pyropia endiviifolia extracts using solvents of different polarity. Methods: Chemical characterization of the extracts was performed using gas chromatography. The anticancer activities of the extracts were evaluated by exposing rat glioma (C6), human glioblastoma (U87), and human lung adenocarcinoma epithelial (A549) cell lines to increasing extract concentrations (10-1000 µg mL−1) for 24 and 48 h. In parallel, rat astrocyte and human lung fibroblast (MRC-5) were treated under the same conditions to represent non-transformed cell controls, and permit tumor selectivity evaluations of the extracts. Results: An MTT assay was used to measure cell cytotoxicity. Hexane, chloroform, and ethanol extracts reduced glioma and lung cancer cell viability. The hexane and ethanol extracts of P. endiviifolia showed the best antiproliferative effect, decreasing glioma cell viability by 40% at 10 µg mL−1, and the chloroform extract reduced lung adenocarcinoma cell viability by 50% at 46 µg mL−1 after 24 h of treatment. None of the extracts affected the viability of non-transformed cells, as was observed in tumor cells. Fatty acids, fatty alcohols, and phthalate esters were the main compounds identified in the seaweed extracts. Conclusions: Antarctic seaweeds displayed selective antitumor activity against glioma and lung cancer cells, particularly the endemic red alga P. endiviifolia. Therefore, these algae could play an important role as novel prototype molecule source for oncology drug development.